Cardiac parasympathetic activity in severe uncomplicated coronary artery disease. Issue 6 (June 1994) - Nolan, J.; Flapan, A. D.; Reid, J.; Neilson, J. M.; Bloomfield, P.; Ewing, D. J.
Abstract : BACKGROUND--Previous studies have suggested that coronary artery disease is independently associated with reduced cardiac parasympathetic activity, and that this is important in its pathophysiology. These studies included many patients with complications that might be responsible for the reported autonomic abnormalities. OBJECTIVE--To measure cardiac parasympathetic activity in patients with uncomplicated coronary artery disease. PATIENTS AND METHODS--44 patients of mean (SD) age 56 (8) with severe uncomplicated coronary artery disease (symptoms uncontrolled on maximal medical treatment; > 70% coronary stenosis at angiography; normal ejection fraction; no evidence of previous infarction, diabetes, or hypertension). Heart rate variability was measured from 24 hour ambulatory electrocardiograms by counting the number of times successive RR intervals exceeded the preceding RR interval by > 50 ms, a previously validated sensitive and specific index of cardiac parasympathetic activity. RESULTS--Mean (range) of counts were: waking 112 (range 6-501)/h, sleeping 198 (0-812)/h, and total 3912 (151-14 454)/24 h. These mean results were unremarkable, and < 10% of patients fell below the lower 95% confidence interval for waking, sleeping, or total 24 hour counts in normal people. There was no relation between the severity of coronary artery disease or the use of concurrent antianginal drug treatment and cardiac parasympathetic activity. CONCLUSION--In contrast with previous reports no evidence of a specific independent association between coronary artery disease and reduced cardiac parasympathetic activity was found. The results of previous studies may reflect the inclusion of patients with complications and not the direct effect of coronary artery disease itself.